Psychological Formation of Patriotic Feeling in Students and its Importance in Education - Mamirovich, Boltaboev Abdugani (Indonesian Journal Publisher, 2025)
This study aims to examine the psychological processes behind the formation of patriotic feelings in students and explore their significance within educational environments. Using a normative-qualitative method, the research synthesizes classical psychological theories—such as those of Erikson, Bandura, Piaget, Kohlberg, and Vygotsky—with contemporary educational practices. Data were analyzed through literature review and conceptual synthesis to identify how emotional, cognitive, moral, and social dimensions influence the development of patriotism among students. The findings reveal that patriotism is not simply taught through factual instruction or ceremonial practice but is internalized through meaningful emotional experiences, critical reflection, and social modeling. Key factors that support this development include emotional attachment to cultural heritage, identity formation through history and traditions, moral reasoning through civic education, and community-based learning that fosters a sense of collective responsibility. Teachers play a vital role as both models and facilitators in this process. Ultimately, the study concludes that fostering a psychologically rooted and ethically informed patriotism requires a holistic educational approach—one that integrates emotional literacy, moral inquiry, and inclusive civic engagement to promote responsible and compassionate citizenship.